PENGARUH PENGGUNAAN MEDIA FLASH CARD TERHADAP KEMAMPUAN BERHITUNG PERMULAAN ANAK USIA DI TK PONTIANAK - Wintia, Sisilia Lilik; Ali, Muhamad; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to defermine differences in the ability to count beginning of children before and after the implementation of flash card media. This research method is a quantitative type of experiment with one-group pretest-posttest design. Data collection techniques using observation and documentation. The sample in this study was children aged 5-6 years in the B2 group consisting 0f 15 girls and 12 boys. The location of this research is TK Bruder Nusa Indah Pontianak Kota. The results of this study that there is a significant influence, this is a evidenced by the average acquistion of children at pretest (before treatment) and the average child at posttest (after treatment). Then the results of the uji-t are calculated so that the results show that there is a difference in the ability to child after being treated using flash card media. This proves that use of real or concrete media such as the use of flash card media has a strong influence on the ability to count in the beginning of the child as evidenced by testing the effect size.Keywords: Children Age 5-6 Years, Early Numeracy Skills, Flash Card Media